Characterization of a new reference class ionization chamber - Maphumulo, Nkosingiphile (My University, 2021)
The aim of this study was to determine the clinical dosimetric performance of a new 3D ionization chamber (PTW-31021) designed for measurements in both standard and nonstandard clinical beams. Beam quality correction factors for standard beams and field output factor correction factors for nonstandard beams were derived, and recommendations were made on the smallest field for which the detector can still provide reliable results. All measurements were performed using a Siemens Primus linear accelerator and a Theratron Equinox Cobalt-60 teletherapy unit. The long term stability of the PTW 31021 was evaluated in the Cobalt-60 beam. The effective point of measurement for the PTW-31021 was determined by comparing the relative depth ionization curve measured with the PTW-31021 set up to the reference point as defined by the manufacture, to the relative depth ionization curve measured with an Advanced Markus chamber (PTW-34045). The energy dependence of the PTW-31021 was determined by comparing the absorbed dose rate measurements in water using the PTW-31021, to absorbed dose rates measured with a Farmer ionization chamber (PTW-30013) and the PTW-34045 in photon and electron beams under similar reference conditions, respectively. The small field ionization chambers used to determine the field output factors were the PTW-31018 microlion liquid ionization chamber, PTW-60012 unshielded diode, PTW-60019 microdiamond, PTW-31016 3D pinpoint ionization chamber and PTW-31010 Semiflex ionization chamber. All measurements in water were performed using the PTW-MP3 water phantom. The PTW-31021 long term stability was found to be within 0.3%, in agreement with manufacture specifications and international recommendations of the IEC 60730. The linearity of detector response measured over a range of monitor units was also found to be within international recommendations. The effective point of measurement was found to be displaced from the reference point suggested by the manufacture by 1.3 ± 0.1 mm upstream for the chamber mounted parallel to the beam axis and 1.4 ± 0.1 mm towards the source for the perpendicular orientation. The results of the energy dependence tests showed that the PTW-31021 is energy dependent for high energy III photons and electrons, and the use of the detector in beam qualities different from the calibration beam, will require a correction factor for energy dependence. Field output factor correction factors for the PTW-31021 were determined for field sizes: 8 x 8, 6 x 6, 4 x 4, 3 x 3, 2.5 x 2.5, 2 x 2, 1.5 x 1.5 and 1.2 x 1.2 cm2 in accordance with the IAEA TRS-483 code of practice [22]
A thesis submitted in fulfilment of the requirements for the degree of Master of Science in Physics to the Faculty of Science, School of Physics, University of the Witwatersrand, Johannesburg, 2021